A Review and Interspecific Comparison of Nocturnal and Cathemeral Strepsirhine Primate Olfactory Behavioural Ecology - Ian C. Colquhoun (International Journal of Zoology)
This paper provides a comparative review of the known patterns of olfactory behavioural ecology among the nocturnal strepsirhine primates and the cathemeral lemurid genus Eulemur. Endemic to Madagascar, all Eulemur species exhibit both diurnality and nocturnality (i.e., cathemerality), and are gregarious, making them an interesting group of taxa to compare with the nocturnal strepsirhines. This paper represents the first comparative review of patterns of olfactory communication among the nocturnal strepsirhines and the cathemeral Eulemur species. Inductive assessment of these comparative data indicates that olfactory communication serves multiple functions in both groups, including individual recognition, sex recognition, indication of social dominance, and coordination of mating behaviour. However, the urine-washing behaviour characteristic of many nocturnal strepsirhines has no clear homologue among Eulemur species (although the latter may use urine droplets in scent marking). Despite sparse and scattered comparative data, it appears that Eulemur species exhibit different olfactory communication patterns that are associated with differing social organizations in this genus.